1995
DOI: 10.1366/0003702953965362
|View full text |Cite
|
Sign up to set email alerts
|

Linear Raman Spectroscopy on Droplet Chains: A New Experimental Method for the Analysis of Fast Transport Processes and Reactions on Microparticles

Abstract: A new experimental method for the analysis of mass and energy transport and reactions on microparticles is presented. A chain of microdroplets from a vibrating orifice generator was injected into a quiescent gas phase. Linear Raman spectra from the microparticles and the surrounding gas were taken at different distances from the generator. Concentration changes were measured as a function of droplet lifetime. A period of time of up to 20 ms could be studied with a resolution of 10 μs. An argon-ion laser in a 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The use of monosized droplets,-since they all have the same diameter and refractive index at a designated location-tends to enhance the consequences of the already mentioned MDR peaks, but space and time averaging of the signal is generally used to smooth the resonances (Vehring et al 1995).…”
Section: Spontaneous Raman Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of monosized droplets,-since they all have the same diameter and refractive index at a designated location-tends to enhance the consequences of the already mentioned MDR peaks, but space and time averaging of the signal is generally used to smooth the resonances (Vehring et al 1995).…”
Section: Spontaneous Raman Scatteringmentioning
confidence: 99%
“…Ideally, the integration time of the technique should be much smaller than the time scale of the droplet changes in diameter, refractive index and chemical composition. Vehring et al (1995) investigated the CO 2 desorption from water droplets. In this study, the shift between the peaks corresponding to gaseous CO 2 and dissolved CO 2 is used to separate the liquid and gaseous phases, while the area of the Raman peaks allows measuring concentrations in both phases.…”
Section: Spontaneous Raman Scatteringmentioning
confidence: 99%
“…Laboratory measurements of Raman spectra from levitated microspheres have been performed by numerous investigators [Vehring et al, 1995Schweiger, 1991;Buehler et al, 1991;Bazile and Stepowski, 1994;Vehring, 1998]. These experiments have been performed over various size parameter ranges, where size parameter is defined as the circumference of the sphere divided by the input wavelength.…”
Section: Theory: Raman Scattering From Spheresmentioning
confidence: 99%
“…These experiments have been performed over various size parameter ranges, where size parameter is defined as the circumference of the sphere divided by the input wavelength. The size ranges in these studies were: 20-120 ], 60-120 [Schweiger, 1991], 120-240 [Vehring et al, 1995], 160-400 [Buehler et al, 1991], and 1700-4500 [Bazile and Stepowski, 1994]. For an input laser wavelength of 351 nm, the corresponding droplet radii are approximately 1.1-6.7 /am, 3-6.7 /am, 6.7-13.4/am, 8.9-22.4/am, and 95-250/am, respectively.…”
Section: Theory: Raman Scattering From Spheresmentioning
confidence: 99%
“…Through analysis of resonance peaks they demonstrated that fractional size fluctuations of less than 2 X can be attained. A number of studies (Vehring et al, 1995;Moritz et al, 1996) examined transport processes, such as absorption and desorption of gases from microdroplets, using a modified Berglund-Liu aerosol generator, but used liquid flow rates measured at a downstream~location to determine drodet size. This procedure may yield size within a few percent of the actual size and is not suitable for processes where minute changes in droulets occur in small time intervals.…”
Section: Introductionmentioning
confidence: 99%